A comparative study of the socioeconomic status, academic performance and NCEE scores of the high school seniors of the three Benedictine schools in Pampanga - Pineda, M. Filipina, OSB (Animo Repository, 1977)
This study was conducted primarily to determine whether there is a significant relationship between the socioeconomic status, academic performance and the NCEE results of the senior high students of the three Benedictine Schools in Pampanga. The writer went on further to determine whether there are significant differences among the students' socioeconomic status, academic performance and NCEE results. The subjects in the study were the 142 high school seniors enrolled in the three Benedictine schools in Pampanga during the school year 1976-1977. A survey questionnaire was administered to gather information and determine the socioeconomic status of the subjects. Their scholastic records used were the subjects' final grades and NCEE scores for the same year. The statistical methods used were the standard scores, to transform the grades of the students of the three schools in comparable units means and standard deviations, to determine the performance levels of the students t-tests, to determine the significant difference between the socioeconomic, academic performance and NCEE levels. The Pearson's product-moment coefficient of correlation was then used to determine the degree or relationship between the three variables in the study.